Take the Opportunity Afforded by the COVID-19 Experiences: Progressive Non-growth Policies for Sustainable Lifestyles - Boström, Magnus (Frontiers in Sustainability, 2021)
The COVID-19 pandemic has led to significant restrictions on lifestyles and consumption everywhere. Many consumer practices have been disrupted due to the shutting down of economic and social activities, limiting of mobility in public places, closing of shopping centers and non-essential stores, and closing of borders. These restrictions have had a significant impact on climate emissions. Much public and scholarly attention has been given to the question of whether the pandemic also offers a window of opportunity for long-term sustainability transformation. The article elaborates on this issue by specifically discussing progressive non-growth policies for sustainable lifestyles and reduced consumption. What potential for long-term transformative change results from lifestyle changes like these? How can societies be restructured to take advantage of the experiences from the pandemic? Bottom-up drivers and possibilities for top-down enforcement are both important to consider. The article limits its focus to top-down policy measures with transformative potential related to sustainable lifestyles (reduced consumption) by summarizing and discussing some key policy lessons identified in recent COVID-19 literature. It considers the need to address likely rebound effects and the vested interests in bouncing practices back towards the previous unsustainable “normality.” The argument is generally inspired by post-growth and degrowth perspectives, as the dominant pro-growth, neo-liberal doctrines are seen as unable to transform societies and guide them onto sustainable paths.